DESIGN OF A MECHATRONIC MODULE MEASURING THE VISCOSITY OF SOLUBLE AND LIQUID PRODUCTS - Oybek Kholmatov; Zaynobiddinov Khojiakbar (European Science Publishing, 2024)
This note provides detailed information on the design and functionality of a mechatronic module designed to accurately measure the viscosity of soluble and liquid products under industrial conditions [1]. Combining mechanical, electrical and computational elements, this innovative module offers real-time analysis, control and data visualization capabilities. Key design issues are explored, including sensor selection, actuation mechanisms, material compatibility, and data acquisition techniques [2]. The statement also emphasizes the module's versatility and application in various fields, highlighting innovative features such as modular architecture, self-calibration mechanisms, user-friendly interfaces and connectivity options. Through this commentary, readers will gain insight into the transformative potential of mechatronic solutions to improve product quality, optimize processes, and drive innovation in industrial manufacturing [3].
Keywords: Mechatronic module, Viscosity measurement, soluble products, Liquid products, industrial tools, Sensor technology, Actuation mechanisms, Material compatibility, Data acquisition, real-time analysis, Control systems, Modular design, User interface, Connectivity, Precision engineering, Process optimization, Quality control, Industrial automation, Manufacturing innovation.